Development of Cement Stabilised Compressed Blocks Using Coal Bottom Ash: Influence of the Grain Size on Mechanical and Physical Properties of Blocks - Minane, Jacques Remy; Lawane, Abdou; Madjadoumbaye, Jeremie; Vinai, Raffaele; Zagré, Brice (Civil and Sustainable Urban Engineering, 2023)
This study investigated the physical and mechanical properties of cement-stabilized compressed blocks manufactured with coal bottom ash sourced from a power plant in Niger. Three different grain sizes were used for the production of compressed blocks with a hand-operated press. Thermal, hydric, mechanical, and fire resistance properties were assessed on the samples. It was found that the use of finer bottom ash resulted in lighter blocks with a density of about 1.02 mg/m3 and thermal conductivity in the range of 0.27 – 0.41 W/m·K. The size of the bottom ash used for the production of blocks did not significantly affect the value of mechanical strength. The exposure of blocks to temperatures of 200°C and 400°C did not reduce the strength of the samples. Neat bottom ash blocks can offer better thermal properties than typical building materials and provide acceptable mechanical strength.